San Quentin - Bacon, Lloyd; Hickox, Sid; O'Brien, Pat; Bogart, Humphrey; Sheridan, Ann (Warner, 2008)
Do the crime, do the time. But what happens during the long years spent behind the walls of San Quentin? The penitentiary's new yard captain wants to make those years a time of rehabilitation rather than punishment. But not everyone's buying it. "He's just another copper to me," snarls inmate Red Kennedy. Humphrey Bogart portrays Red, continuing his climb to stardom in this brisk film that's one of a string of Depression-era works combining gangster-movie elements with a Big House setting. Studio mainstay Pat O'Brien plays Steve Jameson, whose carrot-and-stick reforms begin to change Red's thinking. An inmates' strike and a scripture-quoting con who swipes a rifle are among the troubles Jameson faces. And Red is another as he reverts to his old ways and makes a violent break for freedom. [Cover]